High-performance aqueous Zn–MnO2 batteries enabled by the coupling engineering of K+ pre-intercalation and oxygen defects. Issue 28 (6th July 2021) - Han, Kun; An, Fuqiang; Yan, Fengsheng; Chen, Hailong; Wan, Qi; Liu, Yongchang; Li, Ping; Qu, Xuanhui
Abstract : A K + -pre-intercalated α-MnO2 with oxygen defects (KMOd ) is designed as a high-performance cathode for aqueous Zn-ion batteries guided by a coupling engineering strategy. Abstract : Aqueous zinc–manganese dioxide (Zn–MnO2 ) batteries show great promise for grid-scale energy storage but suffer from sluggish reaction kinetics and severe structural instability of the MnO2 cathode. Herein, a K + -pre-intercalated α-MnO2 cathode with oxygen defects (KMOd ) is designed, guided by a new coupling engineering strategy, demonstrating boosted reaction kinetics and improved structural stability of MnO2 . Closely coupled first-principles calculations and experiments reveal that the synergy effects of pre-intercalated K + and oxygen defects are key to the high electronic conductivity, favorable H + diffusion kinetics, enhanced H + /Zn 2+ adsorption/intercalation capability, and improved structural stability of the KMOd cathode. A high energy density of 518 W h kg −1 calculated based on the mass of the cathode and outstanding long-term cycling performance of over 2500 cycles at 2.0 A g −1 with a capacity of 203 mA h g −1 and a retention of 81.3% are achieved. New insights into the structural stabilization effect by adding K2 SO4 additive into the aqueous electrolyte are also revealed. A hybrid charge storage mechanism of non-diffusion controlled Zn 2+ intercalation and diffusion controlled H + intercalation is proposed.